Кариотипы дождевых червей рода Aporrectodea (Oligochaeta, Lumbricidae) фауны Украины - Коцюба, И.Ю.; Власенко, Р.П.; Гарбар, А.В. (Вестник зоологии, 2010)
Анализ кариотипов дождевых червей рода Aporrectodea Oerley, 1885 фауны Украины свидетельствует о диплоидности большинства его представителей (2n = 36 у A. caliginosa, A. longa, A. georgii и 2n = 32 у A. dubiosa). Кариотип последнего описан впервые. При стандартном для рода базовом числе хромосом (х = 18) A. dubiosa составил исключение (х = 16). Два вида рода (A. rosea и A. Trapezoides) являются полиплоидами (х = 18). У A. trapezoides обнаружена новая полиплоидная раса (6n = 108). The karyotype analysis of earthworms of the genus AporrectodeaO erley, 1885 in the fauna of Ukraine shows that most of them are diploid (A. caliginosa, A. longa, A. georgii (2n = 36) and A. dubiosa (2n = 32)). The karyotype of the latter is described for the first time. Under the standard for this genus chromosome number x = 18, A. dubiosa has õ = 16, whereas the standard chromosome number for this genus is 18. Two species of the genus, A. rosea and A. trapezoides, are polyploid (x = 18). The new polyploid race (6n = 108) is discovered in A. trapezoides.